Comparative Study of the effects of Tricogramma pretiosum (Hym., trichogrammatidae) releases and Triflumuron Applications on Epinotia aporema (Lep., Tortricidae) in Birdsfoot Trefoil Seedbeds - Baáo, C.=700 1 Grille, G.
(En, Es)